Olivocochlear Efferents in Animals and Humans: From Anatomy to Clinical Relevance - Lopez-Poveda, Enrique A. (Frontiers in Neurology, 2018)
Olivocochlear efferents allow the central auditory system to adjust the functioning of the inner ear during active and passive listening. While many aspects of efferent anatomy, physiology and function are well established, others remain controversial. This paper reviews the current knowledge on olivocochlear efferents, with emphasis on human medial efferents. The review covers (1) the anatomy and physiology of olivocochlear efferents in animals; (2) the methods used for investigating this auditory feedback system in humans, their limitations and best practices; (3) the characteristics of medial olivocochlear efferents in humans, with a critical analysis of some discrepancies across human studies and between animal and human studies; (4) the possible roles of olivocochlear efferents in hearing, discussing the evidence in favor and against their role in facilitating the detection of signals in noise and in protecting the auditory system from excessive acoustic stimulation; and (5) the emerging association between abnormal olivocochlear efferent function and several health conditions. Lastly, we summarize some open issues and introduce promising approaches for investigating the roles of efferents in human hearing using cochlear implants.